Approximate reformulation a recent non-renormalizable QFT's methodology and Einstein's gravity - Plastino, Ángel Luis (2020)
We revisit, advancing a useful approximation, a recently formulated QFT treatment that successfully overcomes any troubles with infinities for non-renormalizable QFTs [J. Phys. Comm. 2 115029 (2018)]. Such methodology was able to successfully deal, in non-relativistic fashion, with Newton’s gravitation potential [Annals of Physics 412, 168013 (2020)]. Our present approximation to the QFT method of [J. Phys. Comm. 2 115029 (2018)] is based on the Einstein’s Lagrangian (EG) elaborated by Gupta [1], save for a different constraint’s selection. This choice allows one to avoid the lack of unitarity for the S matrix that impaired the proceedings of Gupta and Feynman. Moreover, we are able to simplify the handling of such constraint by eliminating the need to involve ghosts for guarantying unitarity. Our approximation consists in setting the graviton field µν µν φ γφ = , where µν γ is a constant tensor and φ a scalar (graviton) field. The ensuing approximate approach is non-renormalizable, an inconvenience that we are able to overcome in.